Everolimus treatment in patients with hormone receptor-positive and human epidermal growth factor receptor 2-negative advanced breast cancer and a predictive model for its efficacy: a multicenter real-world study - Yujing Tan; Zexi Peng; Hanfang Jiang; Fei Ma; Jiayu Wang; Pin Zhang; Qing Li; Xinzhu Tian; Yuhang Han; Danyang Ji; Binghe Xu; Weihong Zhao; et al. (Therapeutic Advances in Medical Oncology)
Background: Everolimus is beneficial for patients with hormone receptor-positive and human epidermal growth factor receptor 2-negative (HR+/HER2−) advanced breast cancer (ABC). However, some patients developed drug resistance and the well-established predictor for everolimus efficacy was limited. Objectives: The study was designed to evaluate the efficacy of everolimus in different treatment lines and identify several clinicopathological markers to estimate everolimus efficacy in patients with HR+/HER2− ABC. Design: This was a retrospective and multicenter study. Methods: Between 2014 and 2022, more than 2000 patients with tumors who received everolimus were collected from multiple cancer centers in China (National Cancer Center, Chinese PLA General Hospital, Peking University Cancer Hospital & Institute). A training cohort and two validation cohorts were developed. Results: The training cohort included 338 patients. The median progression-free survival (PFS) for everolimus was 5.6 months, with an objective response rate of 25.1% and a clinical benefit rate of 54.4%. PFS was significantly worse from first-line (1L) to second-line (2L) to third-line (3L), with PFS 1L for 13.5 months, PFS 2L for 6.1 months, and PFS 3L for 4.1 months ( p  = 2.9e−6, hazard ratio (HR) = 0.70, 95% confidence interval (CI) = 0.61–0.82). The clinicopathological characteristics, including post-1L everolimus treatment, Ki67 index of more than 40%, more than two metastatic sites at first recurrence, and receiving adjuvant chemotherapy, were independent risk factors for PFS. A predictive model for everolimus efficacy was established using these four factors. In the low-risk group, patients achieved a median PFS of 12.6 months, significantly longer compared to 2.7 months for those in the high-risk group ( p  = 2.4e−64, HR = 9.41, 95% CI = 7.05–12.56). The area under the curve was 0.96, 0.95, and 0.94 for 6-month, 1-year, and 3-year PFS, respectively. Internal validation cohort (PFS 18.4 vs 3.1 months, p  = 3.6e−11, HR = 3.78, 95% CI = 2.49–5.74) and external validation cohort (PFS 13.5 vs 3.1 months, p  = 2.9e−10, HR = 11.53, 95% CI = 4.68–28.37) confirmed its power for estimating clinical benefits of everolimus. Conclusion: A predictive model was successfully established to predict survival outcomes for everolimus in patients with HR+/HER2− ABC, which may provide references for the management of everolimus in Chinese patients with HR+/HER2− ABC.